2019
DOI: 10.29059/cienciauat.v13i2.1141
|View full text |Cite
|
Sign up to set email alerts
|

Impacto ambiental por uso de plaguicidas en tres áreas de producción de melón en la Comarca Lagunera, México

Abstract: El uso intensivo de plaguicidas altamente tóxicos, en la producción de cultivos hortofrutícolas especializados, conlleva riesgos ambientales y sociales, que pueden medirse mediante indicadores de riesgo de plaguicidas, para evaluar el potencial de impacto negativo de estos productos en los ecosistemas y comparar los logros de la implementación de prácticas agrícolas sustentables, en términos de reducción de riesgos, por la utilización de plaguicidas. El objetivo de esta investigación fue estimar el potencial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
9
0
5
Order By: Relevance
“…This situation is consistent with similar situations in other Latin American countries. For instance, in Mexican melon farms without a wellestablished commercial chain, farmers were found over applying the same pesticide or mixing up to six different pesticide products, leading to toxic residue accumulation in fruit, environmental contamination, and farmer intoxication (Vargas-González et al, 2016). In another study by Calderón et al (2022), the presence of 22 pesticide residues in vegetables sold in supermarkets and farmers markets in Chile and Mexico was evaluated, and the dietary risk was estimated.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is consistent with similar situations in other Latin American countries. For instance, in Mexican melon farms without a wellestablished commercial chain, farmers were found over applying the same pesticide or mixing up to six different pesticide products, leading to toxic residue accumulation in fruit, environmental contamination, and farmer intoxication (Vargas-González et al, 2016). In another study by Calderón et al (2022), the presence of 22 pesticide residues in vegetables sold in supermarkets and farmers markets in Chile and Mexico was evaluated, and the dietary risk was estimated.…”
Section: Resultsmentioning
confidence: 99%
“…Similar works were done by Muhammetoglu & Uslu (2007) in Kumuluca, Turkey, an area known for intensive use of pesticides, and is considered a tool for environmental impact studies of Integrated Pest Management. In melon crops this type of study was conducted in the Lagunera region, Mexico by Vargas-González et al (2019), they identified the pesticides and the production areas with the greatest negative environmental impact.…”
Section: Methodsmentioning
confidence: 99%
“…Number of active ingredients and applications of various pesticide types applied per bell pepper campaign in theChancay-Huaral valley, Lima (2018-2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…embargo, la restricción de la utilización de estos insumos tiene como consecuencia bajos rendimientos en los cultivos (Storck et al, 2017;Vargas-González et al, 2019). Además, se caracteriza por practicar una labranza intensiva y los agricultores no prestan atención a la fertilidad del suelo a largo plazo, ignoran los procesos que lo mantienen (Gliessman, 1998) y utilizan herbicidas para el control de arvenses (Gliessman, 1998;Pengue, 2001).…”
unclassified